Türk-İslam edebiyatı çerçevesinde XIV-XVI. Asır Anadolu sahası divanlarında Kur’an - Coşar, Müberra (My University, 2013)
Türk-İslam edebiyatının temel kaynağı Kur’an-ı Kerim’dir. Edebî eserlerin sahipleri olan şairler ve müellifler tarafından her zaman istifade edilen bu kaynağın etkisi geniş bir sahaya yayılmıştır. Bu çalışma, XIV.-XVI. yy’lar arasında tertip edilmiş divanlardaki Kur’an-ı Kerim tesirini konu edinmektedir. Söz konusu asırlardaki edebî faaliyetler ve Türk-İslam edebiyatının kaynağı olarak Kur’an-ı Kerim’i temel alan giriş bölümünden sonra Kur’an âyet ve sûrelerinin beyitlerdeki tezahürlerinin incelendiği gelmektedir. İkinci bölümde ise örnek beyitler yer almakta, son olarak da XIV.-XVI. yy divanlarında geçen âyetlerin belli başlı konu indeksi bulunmaktadır. slam Edebiyatı, Türk Dili ve Edebiyatı, Kur’an-ı Kerim, Divan.

The main resource of Turkish-İslamic Literature is the Holy Qoran. The effect of this resource which is always utilized by poets and writers who are owners of literary works has spread a wide area. This study deals with the Holy Qoran’s effect in the diwans composed between XIVth and XVIth centuries. After the introduction part which takes the Holy Qoran as a resource of literary activities in the related centuries and of Turkish-İslamic literature, the first part comes, in which signs of Qoran’s verses (ayaths) and chapters (surahs) in couplets are examined. As to the second part, example couplets are occupied and as a conclusion relating to the verses (ayaths) stated in the diwans of XIVth and XVIth centuries index of principal subjects is available. Key Words: Turkish-İslamic Literature, Turkish Language and Literature, the Holy Qoran, Diwan.
Keywords: İslam Edebiyatı, Türk; İslam Tarihi; Kur’an-Kerim